ROLE OF NANOTECHNOLOGY IN CURRENT ADVANCEMENT VACCINE DEVELOPMENT FOR COVID-19 - Mohanty, R (Journal of Global Pharma Technology, 2024)
The most recent human coronavirus known as COVID-19(SARS-CoV-2) has already spread around the world. This review describes the accumulated knowledge of the previous SARS-CoV, MERS-CoV infections and aim to help understand the newly emerged SARS-CoV-2 infection. Advances in nanotechnology over the past decades to develop new nanomaterials and step forward in the application of new technology tools. Finally nanotechnology approach describes vaccine development and therapeutics drugs developed nanomedicines which are currently undergoing clinical trial to become innovative alternatives for overcoming COVID-19 vaccine. Nanoparticles are non-toxic antiviral showed great promise to provide nano vaccine against viral infection. Keywords: Nanotechnology, Vaccine Development, COVID-19.